Struktur Argumentasi pada Bagian Hasil dan Pembahasan Penelitian Tindakan Kelas: A Systematic Literature Review - Silvi Nabilatul Hasanah; Felicia Quthrotun Nada; Silfi Putri Suciyati; Dwi Nur Lailiya Rahmadani; Imron Fauzi (Advances In Education Journal, 2026)
This study examines the structure and patterns of argumentation in the results and discussion sections of Classroom Action Research (CAR) through a Systematic Literature Review (SLR). Although CAR is widely applied to improve classroom practices, the quality of academic argumentation in reporting findings varies considerably. This review follows systematic procedures, including identification, screening, eligibility assessment, and inclusion, and employs qualitative content analysis to explore rhetorical structures and argumentation patterns. The findings reveal that most CAR reports include several key rhetorical moves, namely the presentation of findings, interpretation, comparison with previous studies, pedagogical reflection, and teaching implications. However, the analysis also shows that a significant number of studies remain predominantly descriptive, with limited integration of theoretical frameworks and insufficient depth in analytical interpretation. More specifically, many articles report improvements across action cycles without critically linking empirical evidence to existing theories or prior research. This study contributes to the literature by proposing a conceptual framework that integrates empirical findings, reflective practice, and theoretical perspectives to strengthen academic argumentation in CAR reporting. The novelty of this study lies in its integrative analysis of the relationship between rhetorical structure, argumentation patterns, and the methodological characteristics of CAR within a systematic review framework